IFAS Community Development: In Search of a Common Understanding of Community - Mark A. Brennan (EDIS, 2004)
This paper is the first in a series of discussions on community development. This series will include specialized papers on civic engagement, community action, and other topics important to the development of community. This document is FCS 9205, one of a series of the Department of Family, Youth and Community Sciences, Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: July 2004.